2020
DOI: 10.1136/bmjdrc-2019-000935
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of impaired awareness of hypoglycemia and severe hypoglycemia among people with insulin-treated type 2 diabetes: The Dutch Diabetes Pearl Cohort

Abstract: ObjectivePeople with type 2 diabetes on insulin are at risk for hypoglycemia. Recurrent hypoglycemia can cause impaired awareness of hypoglycemia (IAH), and increase the risk for severe hypoglycemia. The aim of this study was to assess the prevalence and determinants of self-reported IAH and severe hypoglycemia in a Dutch nationwide cohort of people with insulin-treated type 2 diabetes.Research design and methodsObservational study of The Dutch Diabetes Pearl, a cohort of people with type 2 diabetes treated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 44 publications
2
34
1
7
Order By: Relevance
“…Regarding the effect of oral antidiabetic drugs on hypoglycemia, some studies showed that the use of sulfonylureas and biguanides affected the occurrence of hypoglycemia in patients with T2DM [ 26 , 34 , 35 ]. Due to the large amount of insulin administration in our patients, oral antidiabetic drugs had little effect on hypoglycemia, so they did not enter the model.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of oral antidiabetic drugs on hypoglycemia, some studies showed that the use of sulfonylureas and biguanides affected the occurrence of hypoglycemia in patients with T2DM [ 26 , 34 , 35 ]. Due to the large amount of insulin administration in our patients, oral antidiabetic drugs had little effect on hypoglycemia, so they did not enter the model.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Warren et al it could be shown that patients with less hypoglycaemia awareness also reported hyperglycaemia symptoms at a higher glycaemic level [17]. Hypoglycaemia unawareness is about twofold more often present in patients with type 1 diabetes than in patients with type 2 diabetes [21,22]. This could be one explanation for the higher HbA1c threshold in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Severe hypoglycaemia occurs at a rate of 1.3 episodes per person per year in people with type 1 diabetes; but its occurrence is extremely skewed, with only 40% of individuals experiencing an episode in any one year, and 10% of adults with type 1 diabetes contributing nearly 70% of all episodes in the year, with many of these people reporting recurrent events [ 34 ]. Interestingly, a recent study of people with insulin-treated type 2 diabetes in the Netherlands described only slightly lower prevalence of severe hypoglycaemia (32%) [ 35 ]. Impaired awareness of hypoglycaemia is a major risk factor in both types of diabetes.…”
Section: The Evolution Of Acute Responses To Hypoglycaemia Over Timementioning
confidence: 99%